MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS VII - Paneo, Wahyuni; Hulukati, Evi; Bito, Nursiya (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The This research aims to improve students' numeracy literacy skills in algebraic material using a Problem Based Learning model. This Classroom Action Research was conducted at SMP Negeri 3 Suwawa for the 2023/2024 academic year. The research subjects were 30 class VII students and a mathematics teacher. The data collection techniques used were in the form of observations and tests, with research instruments in the form of observation sheets of teacher and student activities as well as tests. This research took place over two cycles. This can be seen from observations of teacher activities increasing by 35.49% from 64.51% in cycle I to 100% in cycle II with good and very good criteria. Furthermore, student activities increased by 50.83% from 49.17% in cycle I to 100% in cycle II with good and very good criteria. Students' numeracy literacy abilities also increased by 15.75% from 69.44% in cycle I to 85.19% in cycle II. Thus, the success indicators for teacher observation activities, student observation activities and students' numeracy literacy skills have increased to reach indicators of success in action